THE PROBLEM OF SECULARISM AND RELIGIOSITY IN MODERN PHILOSOPHY (World Bulletin of Social Sciences, 2021)
In the modern world, the principles of secular society dominate, on the one hand, and on the other, the process of the initial revival of religious consciousness, one of the ancient sources of popular culture. That is why religion has become a social institution on the agenda of many issues related to the role and status of modern society. In this sense, a thorough scientific analysis of the categories of “religiosity” and “secular”, which for a long time were mutually opposed, shows the relevance of the subject. The article explores the terms “religiosity” and “secularism” from the point of view of history and logic: commented on the lexical meaning of the word, its comparative and critical analysis of the definitions of different authors. Particular attention is paid to the analysis of the views of modern philosophers on this issue, the analysis of theoretical views proposed by various academic schools. General and specific aspects of the description and approach are highlighted, the author’s own views on them are described and definitions of the concept of “secularization” and “religious” are developed. Based on recent studies, general theoretical conclusions are given.